The effect of sodium bicarbonate ingestion on high-intensity intermittent running and subsequent performance - Price, M. J.; Simons, C. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to determine the effects of sodium bicarbonate (NaHCO3) ingestion on intermittent running and subsequent performance. Eight healthy men volunteered to take part in the study. One hour after the ingestion of either NaHCO3 or placebo (sodium chloride; NaCl) participants undertook 20 × 24-second runs on a motorized treadmill at the velocity eliciting maximal oxygen uptake (100% v-VO2max). After sprint 20 participants performed a run to volitional exhaustion at 120% v-VO2max. Capillary blood samples for blood pH, bicarbonate ([HCO3-]), and lactate ([Bla]) concentration were taken pre and postingestion, every fifth sprint and after the performance run. After ingestion of NaHCO3, blood [HCO3-] increased from resting values (p < 0.05), and the increase in pH approached significance. Blood [HCO3-] continually decreased throughout intermittent exercise (p < 0.05) and decreased further after performance in both trials (p < 0.05). [Bla] was similar in both trials throughout intermittent exercise but was greater at exhaustion for NaHCO3 (main effect for trial; p < 0.05). There was no significant difference in performance of the group between trials (78 ± 22 and 75 ± 22 seconds for NaHCO3 and NaCl, respectively). The intercept of the relationships between [Bla] and [HCO3-] and between [Bla] and pH was greater during NaHCO3 (p < 0.05), whereas the relationship between pH and [HCO3-] was unchanged (p > 0.05). The results of this study suggest that the ingestion of NaHCO3- before intermittent type exercise was sufficient to induce metabolic alkalosis but did not significantly affect performance. However, because significant individual variations in performance were observed, an individual approach to bicarbonate ingestion is recommended based on the intensity and duration of the required performance.